EVENT RELATED ENDOGEN POTENTIAL (P300) IN FIBROMYALGIA - Özlem Baysal,; Cemal Özcan,; Yüksel Ersoy,; Zuhal Ergünay Altay, (Archives of Rheumatology, 2000)
Fibromyalgia is a non-articular rheumatic disorder characterized by chronic vvidespread musculoskeletal pain and tenderness. Cognitive dysfunctions, especially difficulty in concentration, short term memory and sleep disturbances are also common in these patients. P300 being one of the event related endogen potential is used in the evaluation of the cognitive functions. İt is a long latency potential used in some neurologic diseases such as dementia and Parkinson disease and also in psychiatric diseases such as schizophrenia and depression. In this study, we evaluated P300 potential in 14 patients diagnosed as fibromyalgia according to the American College of Rheumatology 1990 criteria. The control group included 13 healthy subjects. To test the P300 response, two different tones of click sound are given both patients and control group. There was no statistically significant difference betvveen the average latency of P300 in the patients (317.8+32.4 ms) and controls (335.4±34.6 ms). |n addition, no statistical difference was observed in the average amplitude of P300 in either group (12.9+7.8 mV, 12.9±6.8 mV, respectively).